The relationship between sleep quality and learning concentration among junior high school students - Hasanul, Fikri; Nurhusna, Nurhusna; Sari, Putri Irwanti; Sari, Yulia Indah Permata; Oktarina, Yosi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Learning concentration is a crucial ability for students to achieve optimal academic performance. Good sleep quality plays a vital role in influencing students' learning concentration. Purpose: To analyze the relationship between nighttime sleep quality and learning concentration among students in grades VII, VIII, and IX. Method: This study employed a cross-sectional design with a correlational approach. A sample of 100 respondents was selected using stratified sampling technique from students in grades VII, VIII, and IX. Data collection was conducted using the Pittsburgh Sleep Quality Index (PSQI) instrument to measure sleep quality and the Mindful Attention Awareness Scale-Adolescent (MAAS-A) to measure learning concentration. Data analysis utilized Spearman Rank correlation test with a significance level of α = 0.05. Results: Spearman correlation test results showed a strong and significant negative relationship between sleep quality and learning concentration (r = -0.770; p < 0.001). Conclusion: There is a significant negative relationship between nighttime sleep quality and learning concentration among students. Keywords: Adolescents; Junior High School Students; Learning Concentration; MAAS-A; PSQI; Sleep Quality.